1997
DOI: 10.1128/jvi.71.5.3554-3562.1997
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the human papillomavirus type 16 E1--E4 protein shows that the C terminus is dispensable for keratin cytoskeleton association but is involved in inducing disruption of the keratin filaments

Abstract: The function of the human papillomavirus (HPV) E4 proteins is unknown. In cultured epithelial cells the proteins associate with the keratin intermediate filaments (IFs) and, for some E4 types, e.g., HPV type 16 (HPV-16), induce collapse of the keratin networks. An N-terminal leucine-rich motif (LLXLL) is a conserved feature of many E4 proteins. In a previous study we showed that deletion of this region from the HPV-1 and-16 E4 proteins abrogated the localization of the mutant proteins to the keratin cytoskelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 43 publications
0
8
0
4
Order By: Relevance
“…HPV encodes proteins that result in inhibition of cell cycle repair 24, 25. In addition, HPV also encodes proteins known to interact with cytoskeletal development 4. Our findings suggest that active squamous metaplasia may support viral replication and protein transcription and consequently result in the appearance of cytologic changes consistent with a diagnosis of LSIL 3, 5.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…HPV encodes proteins that result in inhibition of cell cycle repair 24, 25. In addition, HPV also encodes proteins known to interact with cytoskeletal development 4. Our findings suggest that active squamous metaplasia may support viral replication and protein transcription and consequently result in the appearance of cytologic changes consistent with a diagnosis of LSIL 3, 5.…”
Section: Discussionmentioning
confidence: 73%
“…The efficiency of HPV replication appears to be dependent on host‐cell proliferation and differentiation 3. Recent studies have demonstrated that specific viral proteins expressed during the process of viral replication may induce the cytoskeletal changes in differentiated superficial epithelial cells (i.e., koilocytosis) and lead to basal cell proliferation characteristic of low grade squamous intraepithelial lesions (LSIL) 4, 5. Because SIL nearly always develops in the transformation zone, in which glandular epithelium is replaced by squamous epithelium, it has been proposed that squamous metaplasia may be fertile ground for the development of SIL in women with an HPV infection.…”
mentioning
confidence: 99%
“…The E region encodes the replication and transcription regulatory proteins E1, E2, and the transforming proteins E5, E6 and E7, which are associated with uncontrolled cell proliferation and differentiation [7]. The E4 protein formed by alternative splicing of genes E1 and E1/E4 transcripts (E4-E1) is associated with the release of the virions through the disruption of the cytoskeleton structure [8,9,10]. It's also shown that actin cytoskeleton was altered in BPV-1 E6-transformed cells through E6 interaction with the focal adhesion protein paxillin [11].…”
Section: Referências _______________________________________________ mentioning
confidence: 99%
“…The first evidence of the oncogenic properties of E6 protein came from studies on human tumors cell lineages derivate from uterine cervix where E6 was found expressed and maintained many years after the initial transformation events [9,10,11]. The E6 and E7 gene products are essential in the process of cell transformation and immortalization [10,12].…”
Section: Referências _______________________________________________ mentioning
confidence: 99%
“…A função de E4 ainda não é bem conhecida acredita-se que sua produção esteja ligada à diferenciação terminal dos queratinócitos. Para alguns autores, a proteína E4 seria responsável pela alteração da arquitetura celular, conhecida como coilocitose (Roberts et al 1997;Doorbar et al 1986).O rompimento da arquitetura da célula pode facilitar a liberação de partículas virais (Doobar et al, 1991).…”
Section: -Introduçãounclassified